Topological indices and their correlation with structural properties of carbon nanotube Y-junctions - Khawlah Alhulwah; Ali N.A. Koam; Nasreen Almohanna; Muhammad Faisal Nadeem; Ali Ahmad (Results in Physics)
Carbon nanotubes (CNTs) are tubular nanoforms of carbon atoms arranged in a hexagonal lattice, and junction formation imparts new functionalities to these tubes. Among the various types, Y-junctions, in which a single CNT splits into a Y-shaped structure, have particular importance in nanoelectronics and logic devices due to their special structural and electronic properties. In this work, the calculation of the Balaban, Forgotten, and Zagreb indices for the four types of CNT Y-junctions is carried out using chemical graph theory. The obtained results clearly show that all these topological indices increase progressively across the different configurations of the Y-junctions, which evidences a direct relationship among the structural complexity and stability with their electronic properties.